Tobacco vendor compliance checks: An analysis of variables that predict clerk behavior - Hillier, Nicole R. (2010)
Preventing tobacco vendors from selling tobacco to youth is part of a comprehensive approach to combat youth smoking. The literature shows that clerks who ask for identification tend to refuse sales to minors. The current study examines which factors predicted whether a clerk sold under a variety of scenarios. The study also examined which factors predicted whether a clerk asked for identification since asking for identification consistently predicts selling in the literature. Over the course of 8 years, the local health department conducted 2717 compliance checks on local tobacco vendors using purchase attempts by youth 14-17 years old. For the current study, 2122 of the cases were analyzed. Logistic regression was performed using different predictor variables. Background variables included operation type, town size, and per capita income of the neighborhood. Event variables included clerk gender, youth age, youth race, youth gender, whether the clerk asked for identification, whether the youth provided identification. Asking for identification and youth age predicted selling. Youth age, clerk gender, and being a liquor store predicted asking. Selling after asking for identification was predicted by the youth providing identification and being a bar/restaurant. Selling after identification was provided upon request was predicted by being a bar/restaurant. Age was the only predictor for selling without requesting identification. Asking for identification is the key to compliance. Clerks who did not ask were 45 times more likely to sell tobacco products. However, asking for identification is only the first step in denying the sale. Because youth who provided ID were more likely to be sold to than those who did not, it is clear that clerks must follow through by looking at the ID card and accurately calculating age. Clerks may assume someone is old enough just because the patron presents identification, even though the ID card proves the youth is under 18. It seems as though clerks who do not ask for identification assume that they can effectively determine age by the way someone looks. If a youth is older, they are more likely to appear as though they are 18, so the clerk is less likely to verify age. Recommendations include training clerks to effectively verify age for everyone, even if they appear old enough. Tobacco licensing is also recommended, as well as consequences for the establishment, not just the clerk because if management was more concerned about illegal sales perhaps the culture of the store could influence clerk behavior, and clerk behavior is the key to compliance. Future directions for research include continuing to monitor tobacco sales to minors using mixed methods of research. Several methods of data collection are necessary to have a clear picture of tobacco sales to minors to in turn affect youth access to tobacco commercially. Several methods should be utilized to gather information from youth smokers and clerks, as well as continued compliance checks